Etnobotani Tumbuhan sebagai Bahan Tambahan Pangan oleh Masyarakat Suku Dayak Bakati’ di Dusun Segiring Kabupaten Bengkayang - Syamswisna Syamswisna (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Ethnobotany is a community tradition of using plants to meet their daily needs, which is a legacy from generation to generation. This study aimed to identify the types of plants used as food additives by the Dayak Bakati Tribe in Segiring Hamlet, Bengkayang Regency, West Kalimantan Province. This study used descriptive methods, made direct observations at the research site, and conducted interviews with informants. The informants are women from the Dayak Bakati Tribe who use plants as food additives and live in Bengkayang Regency. Data was collected using triangulation, namely interviewing informants, observing, and documenting photographs for the documentation of the plant. Information on plants used for ingredients added to food is identified to determine the scientific name. Plants used as food additives by the Dayak Bakati' Tribe in Dusun Segiring, Bengkayang Regency, are 40 species consisting of 24 Families, namely: Zingeberaceae, Apiaceae, Solanaceae, Rutaceae, Fabaceae, Liliaceae, Oxalidaceae, Myrtaceae, Amaryllidaceae, Araliaceae, Lauraceae, Anacardiaceae, Arecaceae, Laminaceae, Euphorbiaceae, Polygonaceae, Piperaceae, Gnetaceae, Bromeliaceae, Pandanaceae, Poaceae, Apiaceae, Sapindaceae, and Strombociaceae. The leaves of the plants Arytera littoralis and Lepionurus sylvestris are used by the Dayak Bakati' Tribe as additional cooking ingredients because they give a taste and aroma like mice. The parts of the plant used are bark and stems, leaves, seeds, tubers, rhizomes, and fruit. The part of the plant that is often used is the leaf. Processing is by slicing/ cutting into small pieces, mashed, and the plant organs utilized are directly inserted into the food being processed. Plants as food additives do not have side effects, they are better used than seasonings containing chemicals.